Innovative ways of special endurance of skaters in the competition period - Kugayevskiy, S. O. (Physical Education of Students, 2013)
The purpose of the study - to propose innovative methods to improve special endurances of the skaters in the competition period. The state of the matter in the practice of preparation of the skaters is considered. It is marked metabolic modes competitive programs skaters on the principle of selective M.R. Smirnov. This is an indicative plan of training microcycle training dancing couple. It is shown that the use of the principle of selective metabolic mode M.R. Smirnov in practice allows comprehensive training skaters to influence the level of development of functional capabilities athlete. It was found that the use of this technique allows us to make training process more manageable by monitoring training loads. It is offered prospects of further studies to optimize the training process of the skaters in the annual cycle of training.